2020
DOI: 10.3390/ijerph17061998
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of West Nile and Usutu Viruses Circulation in Domestic and Wild Birds in Wetlands of Mali and Madagascar in 2008

Abstract: The geographical distribution and impact on animal and human health of both West Nile and Usutu viruses, two flaviviruses of the Japanese encephalitis complex, have been increasing during the past two decades. Both viruses circulate in Europe and Africa within a natural cycle between wild birds and mosquitoes, mainly from the Culex genus. We retrospectively analyzed sera from domestic and wild birds sampled in 2008 in two wetlands, namely the Inner Niger Delta, Mali, and the Lake Alaotra area, Madagascar. Sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…We hypothesise that the abundance of viruses with zoonotic potential is likely to be similarly affected by host age as the non-zoonotic viruses identified here. This is supported by previous studies; for example, influenza A virus is more prevalent in juvenile than adult birds [82], and seroprevalence against influenza A and flaviviruses such as Usutu virus can be higher in adult birds [33,83]. The spillover risk of a broad range of viruses, including half of the families of bird-infecting viruses identified here as being differentially abundant according to bird age (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…We hypothesise that the abundance of viruses with zoonotic potential is likely to be similarly affected by host age as the non-zoonotic viruses identified here. This is supported by previous studies; for example, influenza A virus is more prevalent in juvenile than adult birds [82], and seroprevalence against influenza A and flaviviruses such as Usutu virus can be higher in adult birds [33,83]. The spillover risk of a broad range of viruses, including half of the families of bird-infecting viruses identified here as being differentially abundant according to bird age (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…A competitive enzyme-linked immunosorbent assay (cELISA, ID Screen West Nile Competition Multi species ELISA kit, IDvet, France) was used for the detection of flavivirus antibodies (IgG and IgM) in sera [ 27 ] from humans, dogs and horses, according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Several other studies have shown the co-circulation of USUV and WNV viruses in humans and animals, particularly in Europe [ 26 , 27 ]. Horses, dogs, domestic birds and chickens have been identified as accidental hosts of USUV and WNV [ 7 , 20 , 28 , 29 , 30 , 31 ]. Horses are known as a species particularly susceptible to WNV and USUV infection, and are considered as valuable sentinels of the risk of WNV epizootic transmission [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A WNV serological survey of domestic pigeons in Nigeria reported a seroprevalence of 3.5% [ 39 ]; which is close to the 4.76% rate found in our study. Another study conducted in Mali showed the presence of USUV and WNV antibodies in other species of domestic bird (duck and chicken) [ 30 ]. A large-scale study on domestic pigeons in Burkina Faso would make it possible to better situate their share in the circulation of USUV and WNV.…”
Section: Discussionmentioning
confidence: 99%